The B-Domain Lysine Patch of pRB Is Required for Binding to Large T Antigen and Release of E2F by Phosphorylation - Brown, Vivette D. (American Society for Microbiology, 2002)
Cell cycle-dependent, site-specific phosphorylation of the retinoblastoma protein, pRB, is mediated by cyclin-dependent kinases (CDKs) and regulates the binding of pRB to many proteins. We previously showed that the interaction of pRB with E2F on DNA was regulated by the accumulation of phosphate groups on pRB. Here we show that positively charged lysine residues in the B domain of pRB are necessary for the release of pRB from E2F on DNA following phosphorylation by cyclin E-cdk2 kinase. These lysine residues are also important in the binding of the simian virus 40 large T antigen (TAg) to pRB, and mutation of these lysines to arginines alters the dependency of the pRB-TAg interaction on phosphorylation of pRB.